Preparation and Characterization of Bi2-O3-M2o5 (M =P,As, V) Oxide Ion Conductors - Lee, Siew Ling (2004)
Bi203-M205, M = P, AS, V systems and related materials were prepared by solid state reactions. The phase purity of the materials was determined by X-ray diffraction (XRD). Further characterization using ac impedance spectroscopy and differential thermal analysis (DTA) were carried out on single phase materials. Besides, inductively coupled plasma-atomic emission spectrometry (ICP-AES), density measurement, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), Fourier-transform i n h e d (FT-IR) spectroscopy and Rarnan spectroscopy were also performed on selected materials. The crystal system and space group of the single phase materials were determined. Two narrow solid solution series were formed in xBi2O3-P205: 5.5 I x I 6 and 7 I x 5 7.25. In DTA study, a phase transition was clearly seen in Bi7P013 and Bi~gP40~a~t .-856 0°C.XRD shows that single phase materials were formed in xBi203-As205 binary system when x = 5, 5.5, 5.667, 5.75, 6 and 7. Among these, materials in the composition range of 5 5 x 5 6.25 appeared to be solid solutions. Attempts to synthesize materials of composition of xBi203-As2051, I x I 4 were unsuccesshl. Single phase materials were formed in xBi203-V205 binary system, 5 I x I 6 and x = 7. A phase transition was observed in Bi17V303a3n d Bi23V404.5 at -180°C. However, its origin is unknown. Materials of composition xBi203-M205, 5.5 I x I 6 (M = P) and 5 I x I 6 (M = As, V) are refined in triclinic symmetry with space group of P-I. Meanwhile, monoclinic symmetry was found in materials where x = 7, 7.25 (M = P) and x = 7(M = As, V). The XRD and IR patterns of both series of xBi203-As205, 5 I x I 6.25 and xBi203-V205, 5.5 5 x I 6 solid solutions are very similar since these materials are isostructural. Generally, lattice parameters, volumes and densities of the materials in xBi203-M205 system, M = P, As, V increased with the increase of Bi content. A complete solid solution series was formed in the Bi22P4043-Bi22As4043, Bi22P4043- Bi22V4043, Bi22As4043-Bi22V4043, Bi23P40~.5-Bi23As4044.5, Bi23P404.5-Bi23V4044.5, Bi23A~4044.5-Bi23V4044B.5i1, 2P2023-Bi 12A~2023, Bi 12P2023-Bi12V2023, Bi12As20~- Bi12V202a3n d Bi7AsO13-Bi7V013s ystems. In Bi7PO13-Bi7AsO1a3n d Bi7PO13-Bi7V013 systems a two-phase region was seen. All the single phase materials studied above appeared to be oxide-ion conductors. Conductivity increased with increasing vanadium content, followed by arsenic and phosphorus. Among the materials prepared, the highest conductivity is obtained in Bi23V4044.5w ith a 0 value of 1.34 x lo4 ohm" cm" at 300°C. In an attempt to optimize oxide ion conductivity, chemical doping using PbO, S@O3)2, A1203, Ga203, La203, Fe203 etc. was carried out in selected materials, resulting in the formation of limited solid solutions. These materials, however, exhibit conductivity slightly lower than that of the parent materials. Ball milling process has been carried out in the preparation of Bi23V4044.5a nd Bi14P06 in addition to manual grinding prior to fihg of the samples. In ball milling process, high-density, fine-grained powders with uniform grain-size distribution were obtained, resulting in an increase in conductivity and dielectric constants. Sillenite compounds in the Bi203-P205b inary system with Bi:P ratios of 13:l to 16:1 have been synthesized and found to be solid solutions. Substitution of P by V and As in the material where Bi:P = 14:l results in partial and complete solid solutions, respectively. Enhancement in conductivity was observed in these solid solutions with Vdoped materials exhibiting the highest conductivity. Substitution of P by elements such as pb2+, s?+,~ 1 ~~+a,~ ~+e,~ si+4+,,~ e ~an+d ,~ ile~ads +to f ormation of limited solid solutions. Most of these materials have conductivity similar to or slightly higher than that of the parent compound. These materials appeared to be predominantly oxide ion conductors especially at temperatures above 800°C where y + 6' polymorphic transformation occurred.